The role of political ideas in the formation of political thinking - Natela Basilashvili (Periodica Journal, 2022)
The article "The role of political ideas in the formation of political thinking" discusses the essence, purpose, meaning of political ideas and the essential impact that ideas have had on political reality. Political ideas are analyzed from a comparative point of view as one of the means of knowing the political world. The method of comparison is characterized as one of the most effective and timetested means of understanding what political ideas are and how they are used in the political space. Studying political ideas from this point of view allows us to understand more deeply the meaning of political ideas and their further application in their own or other political systems
Keywords: ideas; comparison; comparativists; institutions